2005
DOI: 10.1192/apt.11.2.101
|View full text |Cite
|
Sign up to set email alerts
|

Management of clozapine-resistant schizophrenia

Abstract: The incidence of treatment resistance in schizophrenia (failure to respond to antipsychotic therapy) is about 20%. Factors that may contribute to it include non-adherence (non-compliance) to treatment, comorbid conditions and medication side-effects. The National Institute for Clinical Excellence recommends that clozapine be used for schizophrenia resistant to another atypical antipsychotic. Here we focus on patients who are also resistant to clozapine given in adequate dosage for sufficient duration. Switchin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 34 publications
0
24
0
2
Order By: Relevance
“…For clozapine-resistant schizophrenia, a variety of pharmacological and non-pharmacological approaches, including electroconvulsive therapy (ECT), have been tried as adjunct therapies 6. The reported advantages of various psychotropic drugs that is the most frequently attempted strategy have been known as modest or equivocal 56789. ECT augmentation has been continued ever since the re-introduction of clozapine in the 1990s10 and the effectiveness of ECT in patients on clozapine has been reported in two randomized controlled studies,411 as well as in case reports and open trials 51213141516171819.…”
Section: Introductionmentioning
confidence: 99%
“…For clozapine-resistant schizophrenia, a variety of pharmacological and non-pharmacological approaches, including electroconvulsive therapy (ECT), have been tried as adjunct therapies 6. The reported advantages of various psychotropic drugs that is the most frequently attempted strategy have been known as modest or equivocal 56789. ECT augmentation has been continued ever since the re-introduction of clozapine in the 1990s10 and the effectiveness of ECT in patients on clozapine has been reported in two randomized controlled studies,411 as well as in case reports and open trials 51213141516171819.…”
Section: Introductionmentioning
confidence: 99%
“…Roughly 20% of people suffering from schizophrenia do not improve with first-line antipsychotics treatment and therefore are categorized as individuals with refractory schizophrenia. Some patients can only achieve remission with the use of clozapine (Kerwin and Bolonna, 2005). Although clozapine is well known for superior efficacy over other antipsychotics, it requires careful management of the potential side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Clozapine was the first atypical antipsychotic available in the US market, and since then it has been used as the gold standard for the treatment of refractory schizophrenia (Kerwin and Bolonna, 2005). Clozapine works by decreasing positive symptoms such as hallucinations, delusions, and disorganized thought patterns as well as negative symptoms that include lack of motivation, pleasure, and diminished ability to communicate.…”
Section: Introductionmentioning
confidence: 99%
“…The criteria employed by Kane et al to define treatment-resistant (or treatment-refractory) schizophrenia in the pivotal trial comparing clozapine to chlorpromazine is used frequently in clinical trials and audit settings 26,27. Kane et al classified participants as treatment-resistant if: improvement had not been demonstrated after 3 periods of treatment with antipsychotics (from 2 or more different chemical classes) in the previous 5 years equivalent to 1000 mg/day of chlorpromazine (CPZ) for 6 weeks and participants had had no episodes of good functioning in the previous 5 years, Brief Psychiatric Rating Scale (BPRS) total score ≥ 45, Clinical Global Impressions (CGI) score ≥ 4, and score ≥ 4 on 2 or 4 positive symptoms items 26.…”
Section: Introductionmentioning
confidence: 99%